Synthesis and characterization of silver nanoprism-based nanostructures - Mohammad Mehdi Shahjamali (2013)
Noble metal nanostructures, ranging from a few atom clusters to micrometer-long nanocrystal, have attracted tremendous attention for more than half a century. They have shown the unique physical and chemical properties, which make them promising candidates in a wide range of applications, such as catalysis, electronics, optics, sensing, bioimaging and gene regulation. These properties can be tuned by controlling the structure size, shape and crystallinity, which have been considered as the ultimate goal in synthesis. Metal nanoprisms are a novel class of anisotropic nanomaterials with exceptional optical properties dependent on their sizes, shapes, and compositions. Silver nanoprisms are of particular interest because their surface plasmon resonance bands are readily tunable in the visible and near-IR (NIR) region. The objectives of this thesis focus on synthesis of novel silver-nanoprisms-based nanostructure with better stability and functionality and to study their formation mechanism, optical properties, and their assembly strategies. Therefore, it is desirable to develop novel strategies for the facile and efficient synthesis of silver-nanoprism-based nanostructures with controlled shape and size based on the knowledge of crystal growth mechanisms, and at the same time to explore new possibilities in obtaining structures with unusual properties. In order to achieve the mentioned goals, the following researches have been carried out. First, a general wet chemical approach has been developed for the shapecontrolled gold coating of silver nanoprisms. This method involves the controlled reduction of gold ions on the silver nanoprism (site-selective reduction) in a highly controlled reducing environment by slowly introducing chloroauric acid and Hydroxylamine hydrochloride simultaneously into the Ag nanoprism solution with two separate tubes by using a mechanical syringe pump with specific concentration and infusion rate. By Engineering the total concentrations of HAuCl4 using a seeding procedure and adjusting the process time, different gold coated silver nanoprisms with various morphologies have been obtained, including three unique structures, i.e. edge gold coated nanoprism (Ag@Auframed nanoprism), core-shell structure (Ag@Au) and the triangular nanobox. All the aforementioned structures have better stability than bare Ag nanoprism due to the gold chemical inertness and have better localized surface plasmon resonance (LSPR) tunability. One of the main advantages of this protocol is that it can preserve the initial shape of the particles which is a key factor in preserving the optical properties for different applications. The Ag@Au structure has still single crystalline nature and can have sharp tips depend on the particle's initial morphology. The LSPR band of the Ag@Au can be tune in a ~100 nm range with respect to its original LSPR which makes them good candidate in many application such as LSPR biosensing, bioimaging and energy conversion. Second, the same gold coating protocol has also been applied to synthesize edge gold coated nanoprism (Ag@Au-framed nanoprism) with ultrathin gold deposition on the edges of the nanoprism, upon etching of the silver template we achieved to synthesis surfactant-free high yield triangular gold nanoframe structure with sub-2 nm thickness. Despite previous reported ultrathin nanoframe structure which didn't show any specific LSPR band, this novel nanostructure show highly tunable dipole LSPR throughout visible or near-IR (NIR) region as a function of Au ridge thickness or interior pinhole diameter. The synthetic approaches described are expandable to other noble metals and open up new avenues for the complex buildup of new complex structures with more functionality. Lastly, the same gold coating protocol with some minor changes has also been applied to synthesize bimetallic nanobox with a proper integrity and uniformity, with preserving the initial triangular Ag nanoprism template. The challenge is to deposit gold atoms selectively on all facets of silver nanoprism to create a gold nanocage following by removing of silver part in the next stage and refilling the hole inside the created nanocage to make a perfect nanobox. The LSPR band of created core-shell nanoprism structures can be tuned in a wide range by controlling the Au shell thickness. On the other hand, the hollow cavity makes the encapsulation of materials of interest possible which candidates it for drug delivery, photothermal cancer therapy and other bioapplications.